Quantum Mechanics Calculations: Asymmetric Phosphines for Methanol Carbonylation (Part I) - Phetmung, Hirihattaya (Malaysian Journal of Science, 2009)
This work presents quantum mechanics calculations based on density functional theory(DFT) for the newly designed asymmetric diphosphine ligand 1.1 that can be a promoter for methanol carbonylation. Because of its chiral centers with electron withdrawing and electron donating groups, this is the reason why the different trans-influence and trans effect of complex type Rh(L)Lï‚¢(1.1) would favor the formation of different isomers. Rhodium complexes 1.3, 1.4, 1.5 and 1.6 can be expected to combine high catalytic activity with thermal stability under the mild conditions of the methanol carbonylation process. The difference in energy (ï„E) values and the calculated equilibrium constant clearly indicate that the most stable isomer 1.5 is the initial catalytically active species and should be possible to prepare.